2014
DOI: 10.1007/s10565-014-9271-8
|View full text |Cite
|
Sign up to set email alerts
|

Presence of nanosilica (E551) in commercial food products: TNF-mediated oxidative stress and altered cell cycle progression in human lung fibroblast cells

Abstract: Silica (E551) is commonly used as an anti-caking agent in food products. The morphology and the dimension of the added silica particles are not, however, usually stated on the food product label. The food industry has adapted nanotechnology using engineered nanoparticles to improve the quality of their products. However, there has been increased debate regarding the health and safety concerns related to the use of engineered nanoparticles in consumer products. In this study, we investigated the morphology and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(77 citation statements)
references
References 35 publications
2
73
0
2
Order By: Relevance
“…80 Cell culture and animal feeding studies suggest that high levels of SiO 2 nanoparticles may cause adverse effects, such as cytotoxicity and generation of ROS. 80,81 A recent study suggested that SiO 2 nanoparticles accumulate in the liver at levels that could cause a health risk. 82 Another study showed that feeding of amorphous SiO 2 nanoparticles to mice for 10 weeks increased the level of ALT (alanine aminotransferase), suggesting a potential adverse effect on the liver.…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…80 Cell culture and animal feeding studies suggest that high levels of SiO 2 nanoparticles may cause adverse effects, such as cytotoxicity and generation of ROS. 80,81 A recent study suggested that SiO 2 nanoparticles accumulate in the liver at levels that could cause a health risk. 82 Another study showed that feeding of amorphous SiO 2 nanoparticles to mice for 10 weeks increased the level of ALT (alanine aminotransferase), suggesting a potential adverse effect on the liver.…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%
“…15,33,49 As a result, many biochemical functions required to maintain cell viability, such as ATP production, DNA replication, and gene expression, may be adversely affected. 33 A number of studies have reported the ability of inorganic nanoparticles to increase the generation of ROS in cells and to produce cytotoxicity, including silicon dioxide nanoparticles, 81 ZnO nanoparticles, 36,126,127 and silver nanoparticles. 15 Some inorganic nanoparticles produce toxicity by generating ions (such as Ag + from silver nanoparticles or Zn 2+ from zinc oxide nanoparticles) that interact with the normal functioning cellular components (such as proteins, nucleic acids, or lipids) required to maintain biochemical processes.…”
Section: Potential Mechanisms Of Action Of Nanoparticle Toxicitymentioning
confidence: 99%
“…It is as commonly used as E551, an anti-caking agent in food products, and considered Bsafe^for human/animal consumption. A study published in 2014 (Athinarayanan et al 2014) investigated its toxic effects on WI-38 (human lung normal fibroblast) cells in terms of cell viability, intracellular ROS levels, cell cycle phase, and the expression levels of metabolic stress-responsive genes. Overall, the results from this study showed that E551 induces a dose-dependent cytotoxicity and changes in ROS levels and alters the gene expression and cell cycle.…”
mentioning
confidence: 99%
“…Coff ee creamers, instant soups and seasoning mixes are products that contain the highest amount of nano-sized SiO 2 (Dekkers et al 2011). Analysis of isolated SiO 2 samples from commercial food products showed the presence of SiO 2 NPs of about 10-50 nm in size (Athinarayanan et al 2014). Also, it was demonstrated that 33% of the food additive SiO 2 (E551) consisted of 10-to 200-nm spherical particles (Dekkers et al 2011).…”
Section: Silicon Dioxide (Sio 2 )mentioning
confidence: 99%
“…Human lung normal fi broblast treated with high concentrations of isolated SiO 2 containing NPs (10-50 nm), showed cellular damage, mitochondrial membrane potential depletion, and ROS generation. Th e cell cycle distribution was altered and the expression of antioxidant enzymes and stress response proteins were modulated (Athinarayanan et al 2014). …”
Section: Silicon Dioxide (Sio 2 )mentioning
confidence: 99%